[Twierdza Wisłoujście] [aut. odbitki Karol Nowaliński]. - Nowaliński, Karol (1935- ). (Karol Nowaliński], 1982)
Przedstawia Twierdzę Wisłoujście, na pierwszym planie nabrzeże w Nowym Porcie, ok. 1890 r.